A phase 1 trial of the HDAC inhibitor AR-42 in patients with multiple myeloma and T- and B-cell lymphomas. Issue 10 (3rd October 2017) - Sborov, Douglas W.; Canella, Alessandro; Hade, Erinn M.; Mo, Xiaokui; Khountham, Soun; Wang, Jiang; Ni, Wenjun; Poi, Ming; Coss, Christopher; Liu, Zhongfa; Phelps, Mitch A.; Mortazavi, Amir; et al.
Abstract: Histone deacetylase inhibitors (HDACi) have proven activity in hematologic malignancies, and their FDA approval in multiple myeloma (MM) and T-cell lymphoma highlights the need for further development of this drug class. We investigated AR-42, an oral pan-HDACi, in a first-in-man phase 1 dose escalation clinical trial. Overall, treatment was well tolerated, no DLTs were evident, and the MTD was defined as 40 mg dosed three times weekly for three weeks of a 28-day cycle. One patient each with MM and mantle cell lymphoma demonstrated disease control for 19 and 27 months (ongoing), respectively. Treatment was associated with reduction of serum CD44, a transmembrane glycoprotein associated with steroid and immunomodulatory drug resistance in MM. Our findings indicate that AR-42 is safe and that further investigation of AR-42 in combination regimens for the treatment of patients with lymphoma and MM is warranted. Trial registration: http://clinicaltrials.gov/ct2/show/NCT01129193